Counseling services for school and vocational guidance counselor from the point of view of secondary school students - Abdelrhman Boufares; Aicha bentaleb (Social Empowerment Journal, 2019)
The present study aimed at identifying the level of counseling services for the school and vocational counselor from the point of view of secondary school students, and to reveal the differences in the extent of utilization of these services among the respondents due to gender and specialization. The study included (200) pupils who were chosen in a simple random manner. The researchers used the counseling services scale after confirming its psychometric characteristics. They also adopted the descriptive analytical method. After using the appropriate statistical methods, the results of the study indicated that there are no differences between males and females in their benefit. The results also revealed differences due to the specialization variable. And it is also showed the practice of guidance counselor for information services, guidance and evaluation to a large degree.